Challenges Faced In The Current Methodologies Of Developing Physical Qualities In Students - Niyazov Asqarbay Tolibaevich (Zien Journals, 2024)
The article describes challenges encountered in the existing methodologies used to develop physical qualities in students. As physical education evolves, educators face various obstacles that hinder the effectiveness of traditional and modern approaches. The paper aims to identify these challenges, analyze their impact on student outcomes, and propose potential solutions to enhance the development of physical qualities in educational settings. Addressing the challenges in current physical education methodologies is essential for fostering the holistic development of students. The author states that by identifying and overcoming these obstacles, educators can create more effective and engaging programs that promote lifelong physical fitness and well-being.
Keywords: challenges; technology; methodology